A systematic review on safety and surgical and anesthetic risks of elective abdominal laparoscopic surgery in infants to guide laparoscopic ovarian tissue harvest for fertility preservation for infants facing gonadotoxic treatment - van der Perk, M. E. Madeleine; van der Kooi, Anne-Lotte L. F.; Broer, Simone L.; Mensink, Maarten O.; Bos, Annelies M. E.; van de Wetering, Marianne D.; van der Steeg, Alida F. W.; van den Heuvel-Eibrink, Marry M. (Frontiers in Oncology, 2024)
Background: Infertility is an important late effect of childhood cancer treatment. Ovarian tissue cryopreservation (OTC) is established as a safe procedure to preserve gonadal tissue in (pre)pubertal girls with cancer at high risk for infertility. However, it is unclear whether elective laparoscopic OTC can also be performed safely in infants <1 year with cancer. This systematic review aims to evaluate the reported risks in infants undergoing elective laparoscopy regarding mortality, and/or critical events (including resuscitation, circulatory, respiratory, neurotoxic, other) during and shortly after surgery.Methods: This systematic review followed the Preferred reporting Items for Systematic Review and Meta-Analyses (PRISMA) reporting guideline. A systematic literature search in the databases Pubmed and EMbase was performed and updated on February 15 th , 2023. Search terms included 'infants', 'intubation', 'laparoscopy', 'mortality', 'critical events', 'comorbidities' and their synonyms. Papers published in English since 2000 and describing at least 50 patients under the age of 1 year undergoing laparoscopic surgery were included. Articles were excluded when the majority of patients had congenital abnormalities. Quality of the studies was assessed using the QUIPS risk of bias tool.Results: The Pubmed and Embase databases yielded a total of 12,401 unique articles, which after screening on title and abstract resulted in 471 articles to be selected for full text screening. Ten articles met the inclusion criteria for this systematic review, which included 1778 infants <1 years undergoing elective laparoscopic surgery. Mortality occurred once (death not surgery-related), resuscitation in none and critical events in 53/1778 of the procedures.The results from this review illustrate that morbidity and mortality in infants without extensive comorbidities during and just after elective laparoscopic procedures seem limited, indicating that the advantages of performing elective laparoscopic OTC for infants with cancer at high risk of gonadal damage may outweigh the anesthetic and surgical risks of laparoscopic surgery in this age group.